DAMPAK BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK BAJU KOKO AR-ROYAN DI BILLINIA FACTORY STORE - Mohammad Taufik; Dadin Solihin; Yusup Ansori; Diana Farid (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2026)
Purchasing decisions are a consumer's process in determining product choices that are influenced by various factors, one of which is brand image. This study aims to analyse the influence of brand image on the purchase decision of Ar-Royan Cocoa Shirt products at Billinia Factory Store Purwakarta. The research uses a quantitative approach with a descriptive method. The study population was 11,400 consumers, with a sample of 100 respondents determined using the Slovin formula and simple random sampling techniques. Data analysis was carried out using descriptive statistics, simple linear regression, correlation coefficient, determination coefficient, and t-test through IBM SPSS Statistics version 26. The results showed that brand image was in the very high category (84.07%) and purchase decisions in the high category (83.48%). A value of R = 0.761 indicates a strong relationship, while R² = 0.579 indicates that brand image explains 57.9% of the variation in purchasing decisions, while 42.1% is influenced by other factors, such as price, product quality, promotion, quality of service, lifestyle, and consumer trust. The regression equation Y = 21.689 + 0.742X and the results of the t-test (t = 11.603; Sig. < 0.05) prove that brand image has a positive and significant effect on the purchase decision of Ar-Royan Cocoa Shirt products at Billinia Factory Store Purwakarta.